Prevention of Streptococcus mutans infection of tooth surfaces by salivary antibody in Irus monkeys (Macaca fascicularis). - Evans, R T (1975)
Four irus monkeys (Macaca fascicularis) were immunized with Streptococcus mutans 6715 killed cells and cell products by injection in the vicinity of the major salivary glands and by instillation into the parotid glands via the ducts. After immune group and a sham-immunized control group of monkeys were infected orally with viable strain 6715 organisms. Dental plaque samples were taken at intervals from the buccal and lingual grooves of the first permanent molars. These samples were evaluated for recovery of strain 6715 by cultural methods. In addition, individual samples were taken from 10 representative tooth surfaces and were evaluated by indirect immunofluorescent staining for strain 6715. Results showed that immune monkeys had fewer infected surfaces and fewer organisms on the infected surfaces than the control animals. These studies indicate that salivary antibody to cariogenic streptococci inhibits implantation of these organisms in dental plaque and may be protective against dental caries.